Prometastatic CXCR4 and Histone Methyltransferase EZH2 are Upregulated in SMARCB1/INI1-deficient and TP53-mutated Metastatic Poorly Differentiated Chordoma to the Liver. (28th October 2020) - Murzabdillaeva, A; Elzamly, S; Brown, R; Buryanek, J; Jafri, S; Rowe, J
Abstract: Introduction/Objective: Chordoma is a rare tumor most commonly arising in the sacrococcygeal region from notochord remnants. Usually, these tumors are locally invasive and recurrent, but do not have the capability to metastasize. A newly described aggressive variant called poorly differentiated chordoma is different than conventional chordoma in that it does not have the well-differentiated histologic appearance of conventional chordoma and also exhibits loss of SMARCB1/INI1. Methods: Herein, we describe a case of poorly differentiated chordoma with SMARCB1/INI1 loss, concurrent TP53 mutation and Rb1 loss. Results: The patient is a 55-year-old man with a history of a previously resected sacrococcygeal chordoma, who was found to have new hepatic, lung, and adrenal lesions. Biopsy of the liver showed sheets of malignant epithelioid cells with vacuolated cytoplasm, areas of necrosis, and up to 5 mitoses in one high power field. No physaliferous features or matrix material were seen. After an extensive panel of immunohistochemical markers, the origin of the metastatic tumor could not be determined and the tumor was only positive for Cam5.2, EMA, and CD56. Brachyury was performed due to the patient's previous history and was positive. Genomic testing showed a SMARCB1 mutation, a TP53 mutation, and RB1 loss. Additional markers were performed and the tumor showed a Ki-67 proliferation index of approximately 80%, mutant p53 protein, loss of INI1, and strong expression of prometastatic CXCR4 and the histone methyltransferase EZH2. The most recent follow-up of the patient showed that the patient was receiving palliative care. Conclusion: Poorly differentiated chordoma is a highly aggressive variant of chordoma with few cases reported. This case of SMARCB1/INI-deficient, poorly differentiated chordoma also showed concurrent TP53 mutation and loss of RB1, which resulted in malignant transformation with loss of differentiation, cell cycle progression, up-regulation of prometastatic CXCR4 and the histone methyltransferase EZH2 causing aggressive behavior and metastasis.